QUICK-ASSEMBLED BUILDINGS – A NEW WAY OF ORGANIZING ENERGY EFFICIENT ECOLOGICAL SETTLEMENTS FOR REFUGEES - Petrova, O.; Selikhova, Y. (Municipal economy of cities. Series: «Economy science», 2022)
On the 24th of February, 2022, a hostile invasion of the Russian army began on the territory of our country, along the entire length of the common border, from Luhansk to Chernihiv, as well as from the territory of Belarus and the occupied Crimea. The Russian occupiers are destroying our cities terribly and heartlessly. The occupiers continue their attacks, but they are unable to overcome the strong-minded Ukrainians, courageous soldiers - the Armed Forces, who are defending their land. The city of Kharkiv, which was the first capital of Ukraine, was awarded the honorary title of the city of Heroes, due to persistent resistance to the predatory bombing of military and industrial facilities, educational institutions, health care facilities, as well as civilian and residential facilities. As a result, the rapid evacuation of the city's population to more remote cities in Ukraine or abroad began. Peaceful people were forced to leave and leave their homes for safety, taking only essentials. But, unfortunately, the territories of most Ukrainian cities to which people were evacuated are overcrowded and do not have the necessary number of residential buildings that would provide comfortable conditions for temporary shelter for internally displaced persons. Therefore, this article aims to solve the global problem of today, namely, the creation of comfortable living conditions through new urban planning entities - energy-efficient ecological settlements for refugees. This settlement should provide the most rational organization of space, be compact, energy efficient, adapted to the selected area and fast in implementation, thanks to innovative technologies - prefabricated buildings. The aim of this study is to identify optimal ways to organize energy-efficient ecological settlements for refugees by building compact types of buildings that are energy efficient and quick to implement. Based on this goal, various types of compact buildings that are energy efficient and fast to implement, features of design solutions for residential buildings that are environmentally friendly and energy efficient and three-dimensional solutions for the organization of energy efficient environmental settlements for refugees and internally displaced persons (IDPs).